Influence of portal vein occlusion on portal flow and liver elasticity in an animal model. (25th February 2021) - Chatelin, Simon; Pop, Raoul; Giraudeau, Céline; Ambarki, Khalid; Jin, Ning; Séverac, François; Breton, Elodie; Vappou, Jonathan
Abstract : Hepatic fibrosis causes an increase in liver stiffness, a parameter measured by elastography and widely used as a diagnosis method. The concomitant presence of portal vein thrombosis (PVT) implies a change in hepatic portal inflow that could also affect liver elasticity. The main objective of this study is to determine the extent to which the presence of portal occlusion can affect the mechanical properties of the liver and potentially lead to misdiagnosis of fibrosis and hepatic cirrhosis by elastography. Portal vein occlusion was generated by insertion and inflation of a balloon catheter in the portal vein of four swines. The portal flow parameters peak flow (PF) and peak velocity magnitude (PVM) and liver mechanical properties (shear modulus) were then investigated using 4D‐flow MRI and MR elastography, respectively, for progressive obstructions of the portal vein. Experimental results indicate that the reduction of the intrahepatic venous blood flow (PF/PVM decreases of 29.3%/8.5%, 51.0%/32.3% and 83.3%/53.6%, respectively) measured with 50%, 80% and 100% obstruction of the portal vein section results in a decrease of liver stiffness by 0.8% ± 0.1%, 7.7% ± 0.4% and 12.3% ± 0.9%, respectively. While this vascular mechanism does not have sufficient influence on the elasticity of the liver to modify the diagnosis of severe fibrosis or cirrhosis (F4 METAVIR grade), it may be sufficient to attenuate the increase in stiffness due to moderate fibrosis (F2‐F3 METAVIR grades) and consequently lead to false‐negative diagnoses with elastography in the presence of PVT. Abstract : Portal occlusion induced by portal vein thrombosis is modeled by inflation of a balloon catheter in the portal vein of pigs. 4D‐flow MRI and magnetic resonance elastography measurements indicate that reduction of the portal venous blood flow results in a decrease of liver stiffness. Portal vein thrombosis may attenuate the increase in stiffness due to moderate fibrosis and lead to false‐negative diagnoses with elastography.